Newly Qualified Teachers’ Well-Being During the COVID-19 Pandemic: Testing a Social Support Intervention Through Design-Based Research - Froehlich, Dominik E.; Morinaj, Julia; Guias, Dorothea; Hobusch, Ulrich (Frontiers in Psychology, 2022)
Around the world, newly qualified teachers are leaving the profession after only a short time working at school. This not only has a negative effect on the capacities of the respective education systems, but also for the teachers themselves, as it often due to factors such as stress and burnout that leads to this decision. The COVID-19 pandemic has exacerbated this situation by adding to the teachers’ workload, uncertainty, and stress. Previous research has investigated strategies that may help teachers improve their well-being and, among other factors, found social support to be an important condition. In this mixed methods design-based research study, we developed a design to enhance social support among newly qualified teachers in their first months working at school. Our quantitative and qualitative results show that the design has positive effects on many aspects of teachers’ well-being in the intervention group both longitudinally (before and after the intervention) and when compared to a comparison group. The findings are being discussed considering the recent changes in the working conditions of teachers as imposed by the COVID-19 pandemic.